من الأهداف الإنمائية للألفية الثالثة إلى أهداف التنمية المستدامة ما بعد عام 2015 : إطار برنامج تنموي من منظور أممي ،عربي ،عراقي (المجلة العراقية للعلوم الاقتصادية, 2018)
The third Millennium Development Goals 2000-2015 engaged a range of priority development issues in order to reduce poverty and promote human dignity, but the achievement ratios realized from developing countries, in general, and Iraq, in particular, did not reach the targeted levels, due to the accumulated challenges, making it the requirement of social justice and governance and ensure the freedoms and achieve sustainable growth an extended and milestone requirement and expressed the essence of sustainable development goals beyond 2015 and that the United Nations is seeking to launch a global blueprint for development in September 2015.